A case report of 131I therapy for Graves' disease patient with hemiagenesis. Issue 8 (February 2019) - Liu, Xuehui; Zhang, Jianping; Meng, Zhaowei; Yu, Hongxu; Gao, Zhimin; Li, Hongjun; Liu, Na
Abstract: Rationale: Thyroid hemiagenesis is a rare congenital dysplasia, whereas a variety of pathological changes may occur in residual thyroid lobe. The most frequently described pathology in residual thyroid lobe is Graves' hyperthyroidism. Although 131 I therapy has been generally recommended as the preferred treatment for Graves' disease (GD), subjects relating to hemiagenesis are very limited, especially in China. Patient concerns: A 43-year-old female patient presented to our hospital on November 2014, with a 1-year history of palpitation, fatigue, and hand tremor. Her situation was getting worse within 2 months. Diagnosis: The thyroid function tests were suggestive of thyrotoxicosis. The technetium thyroid scintigraphy only showed an enlarged right lobe with increased tracer uptake. Then, the agenesis of left lobe and isthmus was confirmed by ultrasound and magnetic resonance imaging (MRI). Thus, a diagnosis of GD with hemiageneis of the left lobe and isthmus of thyroid was made. Interventions: Thiamazole was discontinued because of drug-induced hepatic injury. According to our procedures, the patient was treated by 131 I. Outcomes: Hypothyroidism was observed 3 months after 131 I therapy. After replacement therapy with L-thyroxine (LT4), the state of euthyroid maintained. Lessons: Once hypothyroidism occurs, regular application of LT4 and review of thyroid function is very important. Thus, patients' compliance needs to be strengthened. Besides, we could not convince the family members of our patient to undergo ultrasonographic examination. The genetic factor of the agenesis could not be proved in this case.